An application of geographic information systems (GIS): the utility of victim activity spaces in the geographic profiling of serial killers - Shamblin, Charles Casey (2004)
Today, computer technology is producing new methods of investigation into the complex nature of serial killers; among these are geographic profiles. Yet, due to the lack of proven success, budgetary constraints, and the inherent multifaceted nature of serial murder, these geographic profiles have not been completely embraced by the law enforcement community. Because of this, the academic and law enforcement communities continue to refine and develop new methods to solve serial killer cases. This thesis investigates the possibility of identifying the location of the interaction site of a serial killer and his victims using a commercial geographic information system (GIS) as the primary tool. This will be accomplished by analyzing the daily activities of three hypothetical victims of serial murder. A comparison of survey results from the hypothetical victims of this study and their associates shows evidence that victim activity areas can contribute to serial killer investigations. This new method demonstrates that, instead of costly spatial analysis software used today in geographic profiling, geographic information pertinent to a serial killer investigation can be disclosed using a commercial GIS. The addition of a geographic method that adds the component of time and focuses on the daily routine of the victim will complement existing profile methods and provide investigators with a new tool in understanding serial killer phenomena. A law enforcement perspective of this method and GIS is also presented